1983
DOI: 10.1007/bf00048482
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implantation site on formation of metastases

Abstract: It has been suggested that local factors at the site of growth of a primary tumor might influence the outcome of the metastatic process. Compilation of the data from the literature revealed that growth of tumor cells in the selective medium of the intraperitoneal cavity, of the lymph node and/or of the spleen leads to progression towards a population of cells with a higher metastatic capacity. In search for an experimental model with transplantable rodent tumors that could be used to study the influence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…M04 1-4 cells were derived from the virally transformed murine M04 fibroblast cells upon transfection with a cDNA of human PLAP (type 2). The tumour incidence (100%), latency times, and tumour growth curves found for transfected M04 1-4 cells were similar to results obtained for nontransfected M04 cells which have been documented previously (Mareel et al, 1975;Meyvisch & Mareel, 1982). Our detailed characterisation of the PLAP synthesised by the M04 1-4 cells confirmed that all enzymatic and immunologic properties were conserved, and that it was localised on the outer surface of the plasma membrane of these M04 1-4 cells, making it an ideal target for tumour localisation and imaging.…”
Section: Discussionsupporting
confidence: 89%
“…M04 1-4 cells were derived from the virally transformed murine M04 fibroblast cells upon transfection with a cDNA of human PLAP (type 2). The tumour incidence (100%), latency times, and tumour growth curves found for transfected M04 1-4 cells were similar to results obtained for nontransfected M04 cells which have been documented previously (Mareel et al, 1975;Meyvisch & Mareel, 1982). Our detailed characterisation of the PLAP synthesised by the M04 1-4 cells confirmed that all enzymatic and immunologic properties were conserved, and that it was localised on the outer surface of the plasma membrane of these M04 1-4 cells, making it an ideal target for tumour localisation and imaging.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that s.c. injection of Rama 950 feeders with Rama 900 cells produces a shorter time before the rats become moribund, and hence a possible increase in the rate of metastasis, suggests that such mesothelial cells may also exert a 'feeder' effect at this site, but not at the other two sites in vivo. Variation of metastatic potential with site of implantation has also been observed in other systems (Meyvisch, 1983;Unemori et al, 1984).…”
mentioning
confidence: 73%
“…Moreover, when Rama 900 cells were collected from the ascites of rats originally injected with Rama 900-12 cells and then passaged four times in culture before being reinjected s.c. into the mammary fat pad of fresh intact rats, the original incidence of tumours and metastases was not altered (not shown). This result eliminated the possibility that passage through syngeneic animals and subsequent culture caused changes in cellular behaviour in vivo (Meyvisch, 1983).…”
Section: Morphology Of Cultured Cellsmentioning
confidence: 99%
“…When primary tumor burden was relieved (ftpd. route) (11,19), thereby increasing the life span of the animal, "pea"-size lung tumor nodules were observed (Fig. 1).…”
Section: Methodsmentioning
confidence: 96%